2022
DOI: 10.3389/fpls.2022.958106
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral remote sensing for accurate acquisition of rice phenotypes: Impacts of radiometric calibration and unmanned aerial vehicle flying altitudes

Abstract: As a promising method, unmanned aerial vehicle (UAV) multispectral remote sensing (RS) has been extensively studied in precision agriculture. However, there are numerous problems to be solved in the data acquisition and processing, which limit its application. In this study, the Micro-MCA12 camera was used to obtain images at different altitudes. The piecewise empirical line (PEL) method suitable for predicting the reflectance of different ground objects was proposed to accurately acquire the reflectance of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Altitude will affect the spatial resolution of imagery and different observation angles on the same target. In Luo research [12], there are differences in reflectance value of paddy using 100 m -250 m altitude, which affects the value of the vegetation index. It is found that 100 m altitude is the most stable altitude to produce vegetation index value.…”
Section: Introductionmentioning
confidence: 99%
“…Altitude will affect the spatial resolution of imagery and different observation angles on the same target. In Luo research [12], there are differences in reflectance value of paddy using 100 m -250 m altitude, which affects the value of the vegetation index. It is found that 100 m altitude is the most stable altitude to produce vegetation index value.…”
Section: Introductionmentioning
confidence: 99%
“…Ground remote sensing systems are close to the surface, facilitating more detailed information on rice, but are limited in their coverage due to fixed station locations ( Gnyp et al., 2012 ). In comparison, the application of near-ground UAVs provides significant assistance in improving the temporal and spatial resolution of rice monitoring, with the advantages of cost-effectiveness, operational simplicity, and high efficiency in large-scale monitoring ( Wan et al., 2020 ; Bascon et al., 2022 ; Luo et al., 2022 ; Xu et al., 2022a ). In particular, consumer-grade UAVs equipped with visible and multispectral cameras can conveniently obtain canopy structural parameters and key spectral, color and texture features, which have been widely used to estimate AGB ( Xu et al., 2022b ; Zheng et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Radiometric compensation for images acquired by UAV platforms is inherently challenging due to variations in imaging conditions for each capture. Therefore, an established and systematic procedure is imperative to conduct comprehensive radiometric compensation and generate multispectral images with reflectance [28][29][30].…”
Section: Introductionmentioning
confidence: 99%